Excess Commitment in R&D - Guenzel, Marius; Liu, Tong (Review of Financial Studies, 2026)
Abstract We document that firms exhibit “excess” commitment to R&D projects and examine its consequences for innovation outcomes. Using detailed data on pharmaceutical firms’ clinical trial projects, we find that trial delays, empirically uncorrelated with multiple project-quality measures, substantially reduce firms’ subsequent project-termination propensity. This result remains robust when we use variation in clinical trial site congestion to instrument for unexpected delays. Excess commitment intensifies when CEO compensation has greater stock-price sensitivity and the CEO is responsible for the project’s initiation. Our findings have broader implications: delay-driven commitment reduces new drug project initiations, with further evidence suggesting efficiency losses for firms.